Astrocytogenesis: where, when, and how [version 1; peer review: 2 approved] - Ekin Su Akdemir; Anna Yu-Szu Huang; Benjamin Deneen (F1000Research, 2020)
Astrocytes are the most abundant cell type in the central nervous system and have diverse functions in blood–brain barrier maintenance, neural circuitry formation and function, and metabolic regulation. To better understand the diverse roles of astrocytes, we will summarize what is known about astrocyte development and the challenges limiting our understanding of this process. We will also discuss new approaches and technologies advancing the field.